Problematika Pendidikan Agama Islam di MTs: Tantangan dan Ancaman di Era Society 5.0 (Pusat Riset dan Inovasi Nasional, 2026)
The development of Society 5.0 requires Islamic Religious Education (PAI) learning in MTs to transform into a more adaptive model that integrates technology while maintaining a focus on character formation. This article aims to identify the main problems in PAI learning at MTs and analyze the challenges and threats arising from digital educational changes. This study employs a descriptive qualitative approach through literature review, educational policy analysis, and synthesized findings from the last five years. The results show that the central issues include teachers' digital competence, infrastructure readiness, value degradation due to digital distraction, and the mismatch between students’ character needs and technology-based learning demands. Society 5.0 offers opportunities for technology integration but also brings threats such as misinformation, digital dependency, and weakened value internalization when learning is not holistically designed. This study provides strategic recommendations for teachers, schools, and policymakers to strengthen PAI learning quality relevant to digital-era needs.